Performance of individually-measured vs population-based C-peptide kinetics to assess β-cell function in presence and absence of acute insulin resistance - Varghese, Ron T. (Diabetes Obes Metab, 2017)
AIMS: Standardized, population-based kinetics of C-peptide distribution and clearance are used to estimate insulin secretion from plasma C-peptide concentrations without direct measurement of C-peptide kinetics. We then compared the performance of population-based kinetics to directly measured C-peptide kinetics when used to calculate β-cell responsivity indices. To ensure that population-based kinetics apply to all conditions where β-cell function is measured, subjects were studied in the presence and absence of acute insulin resistance. MATERIALS AND METHODS: Somatostatin was used to inhibit endogenous insulin secretion in 56 nondiabetic subjects. Subsequently, a C-peptide bolus was administered and the changing concentrations used to calculate individual kinetic parameters of C-peptide clearance. In addition, they were studied on 2 occasions in random order using an oral glucose tolerance test (OGTT). On one occasion, free fatty acid (FFA) elevation to cause insulin resistance, was achieved by infusion of intralipid + heparin. Disposition Index (DI) was then estimated by the oral minimal model using either population-based or individual C-peptide kinetics. RESULTS: There were marked differences in the exchange parameters (k(12) and k(21)) of the model describing C-peptide kinetics, but smaller differences in the fractional clearance, i.e. the irreversible loss from the accessible compartment (k(01)), obtained from population-based estimates compared to experimental measurement. Since it is predominantly influenced by k(01), DI estimated using individual kinetics correlated well with those estimated using population-based kinetics. CONCLUSIONS: These data support the use of population-based measures of C-peptide kinetics to estimate β-cell function during OGTT.